Motivation to learn: an international multilevel study on student autonomy and teacher emphasis on content usefulness - Moreno-Murcia, Juan Antonio; Huéscar Hernández , Elisa; León, Jaime; Fin, Gracielle; Nodari Júnior, Rudy José; Valero-Valenzuela , Alfonso; Tristán , José; Gastélum-Cuadras, Gabriel; Zueck Enríquez , María del Carmen; Vargas Vitoria , Rodrigo; Cid, Luís; Monteiro, Diogo; et al. (Anales de Psicología / Annals of Psychology, 2024)
Teacher autonomy support is related to improved student learning. In higher education, few studies relate classroom contextual factors, such as teacher emphasis on content usefulness, and students' motivational characteristics. The aim was to test a multilevel model about the relation between the extent of teachers’ emphasis on the usefulness of class content with student autonomy, and, in turn, on motivation to learn. The participants were 3033 university students enrolled from 1st to 4th grade of Sciences of the Physical Activity and Sport, from universities in Spain (N = 602), Portugal (N = 469), Mexico (N = 1177), Chile (N = 372), and Brazil (N = 413). A multilevel structural equation model was performed, in which participants answered questions about the teacher's emphasis on the usefulness of class content, basic psychological need for autonomy, and motivation to learn. At the group and individual levels, the hypothesis is that the teacher's emphasis on the usefulness of class content predict the student autonomy, in turn, student autonomy predicts student motivation to learn. Results found at the group level and at the individual level the strength of teacher emphasis on class content predicted student autonomy; student autonomy predicted student motivation to learn.